Synthesis and characterization of multiwall carbon nanotubes using microwave heating for removal of heavy metals / Mubarak Mujawar - Mubarak , Mujawar (2015)
Carbon nanotubes (CNTs) are among the most eminent materials in the first rank of the nanotechnology revolution. The most eye-catching features of these structures are their electronic, mechanical, optical and chemical characteristics, which open a way for future applications. A new method is introduced for synthesis of CNTs by gas phase, single stage microwave assisted chemical vapor deposition (MA-CVD) using ferrocene as a catalyst and acetylene (C2H2) and hydrogen (H2) as precursor gases. A fast CNTs growth and ambient reaction condition, lowers the cost, and simplifies the procedure leading to a high yield synthesis of high-quality CNTs with minimal impurity are among the characteristics of the MA-CVD. Production of CNTs depends on various process parameters such as microwave power, radiation time, and gas ratio of C2H2/H2 and further investigation was based on the central composite design (CCD) for optimization. The morphology and structures of multiwall carbon nanotubes (MWCNTs) produced were characterized using Field Emission Scanning Electron Microscope (FESEM), Transmission Electron Microscope (TEM) and Thermo Gravimetric Analysis (TGA). FESEM and TEM analyses revealed that the uniformly dispersed vertical alignment of MWCNTs have diameters ranging from 16 to 23 nm and 30 micron long and high BET surface area of 206 m2/g. The TGA analysis showed that the purity of MWCNTs produced is around 98% purity. Results reveal that the optimized conditions for MWCNTs production were 900 W microwave power, 35 min radiation time, and 0.6 gas ratio of C2H2/H2. Removal of heavy metal from industrial waste water leads to the biggest challenge nowadays due to it the novel MWCNTs samples are tested for performances in the removal of heavy metals. The effect of process parameters such as pH, MWCNTs dosage, agitation speed and adsorption time were investigated using a CCD. The optimization and kinetic study on the removal of Pb (II), Cd (II), Cu (II) and Zn (II) using novel MWCNTs was conducted. Maximum adsorption capacities (qm) for Pb (II), Cd (II), Cu (II) and Zn (II) ions were obtained as 104.2, 88.62, 99 and 90.9 mg/g, respectively. Analysis of results revealed that the optimum conditions for the highest removal (99.9%) of Pb (II) and (98.8%) Cd (II) were recorded to have pH 5, MWCNTs dosage 0.1 g, contact time 22.5 min for Pb (II) and 50 min for Cd (II) and agitation speed of 160 rpm, respectively, with the initial concentration of 10 mg/l. In addition, statistical analysis revealed that the optimum conditions for the highest removal (99%) of Cu (II) and (99.9%) Zn (II) were recorded to have pH 5.5, and pH10 MWCNTs dosage 0.1 and 0.05 g, contact time 35 min for Cu (II) and 60 min for Zn (II) and agitation speed of 160 rpm for Cu (II) and 120 rpm for Zn (II) respectively. The Langmuir and Freundlich isotherm models matched the experimental data very well and adsorption kinetic obeyed pseudo-second for Pb (II), Cd (II), Cu (II) and Zn (II). The results proved that MWCNTs can be used as an effective adsorbent due to the high adsorption capacity as well as the short adsorption time needed to achieve equilibrium.